2018
DOI: 10.30998/scope.v2i02.2307
|View full text |Cite
|
Sign up to set email alerts
|

Using Graphic Organizer as a Media in Students’ Writing Project

Abstract: <p>“Picture tells a thousand words“. It is important that teachers help the students organize their writing which they are learning to build and enhance their writing skill. Graphic organizer is a creative great media for comparing and contrasing text or story and can easily be applied to any kind of topic to help the students understand the differences between the texts or stories. Beside that aim, graphic organizer also helps the students to organize their writing skill and enhance their writing skill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…The finding that graphic organizers (GOs) differ significantly from non-graphic organizers (NGOs) on writing performance is in accordance with earlier studies that found GOs to be an effective strategy to improve writing skills (Ningrum & Crosthwaite, 2020;Rahmat, 2020;Setyowati, Sukmawan, & El-Sulukiyyah, 2020;Anderson et al, 2018;Anggraeni & Pentury, 2018;Maharani, 2018;Wahyuni & Umam, 2017;Vitanofa & Anwar, 2017;Setyowati, Sukmawan, & Nurmansyah, 2017;Jumariati & Sulistyo, 2017;Khalaji, 2016;Aunurrahman, Hamied, & Emilia, 2016;Khatib & Meihami, 2015;Mustafa & Samad, 2015;Meera & Aiswary, 2014;Robinson & Kiewra, 1995). The study evidence that GOs can be used successfully in L2 argumentative writing classes.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that graphic organizers (GOs) differ significantly from non-graphic organizers (NGOs) on writing performance is in accordance with earlier studies that found GOs to be an effective strategy to improve writing skills (Ningrum & Crosthwaite, 2020;Rahmat, 2020;Setyowati, Sukmawan, & El-Sulukiyyah, 2020;Anderson et al, 2018;Anggraeni & Pentury, 2018;Maharani, 2018;Wahyuni & Umam, 2017;Vitanofa & Anwar, 2017;Setyowati, Sukmawan, & Nurmansyah, 2017;Jumariati & Sulistyo, 2017;Khalaji, 2016;Aunurrahman, Hamied, & Emilia, 2016;Khatib & Meihami, 2015;Mustafa & Samad, 2015;Meera & Aiswary, 2014;Robinson & Kiewra, 1995). The study evidence that GOs can be used successfully in L2 argumentative writing classes.…”
Section: Discussionsupporting
confidence: 90%
“…Humor can also be applied in the learning media, as mentioned by (Anggraeni & Pentury, 2018), there are various kinds of media, but visual aids are the appropriate media for learners, particularly young learners. The visual aids which commonly used for teaching English are pictures, really or real objects, drawings, or teacher-made drawings, charts, posters, cartoons, and flashcards (Anggraeni & Pentury, 2018). Thus, it can also be administered in the Educational Career course with some adjustments regarding the course.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 99%
“…To intervene in this issue, utilising graphic organisers (GO) like mind maps in writing classrooms may benefit struggling ESL learners by enhancing their ability to process concepts and understand writing tasks (Lembaga Peperiksaan Malaysia, 2021). Many previous studies on the use of graphic organisers in ESL writing instruction have produced diverse findings (Ewoldt & Morgan, 2018;Puspitawati, 2017;Abdul Aziz et al, 2018;Lingaiah & Dhanapal, 2020;Singh et al, 2020;Anggraeni & Pentury, 2018;Rahmat, 2020). Even though the studies provide insightful perspectives and understanding of ESL writing, their findings do not yield an adequate understanding of the ESL writing phenomenon beyond the context in which they worked.…”
Section: Introductionmentioning
confidence: 97%